2018
DOI: 10.2217/fon-2018-0044
|View full text |Cite
|
Sign up to set email alerts
|

Talking to Patients about Biosimilars

Abstract: Biologic therapies target aberrant pathways in diseases including diabetes, cancer and autoimmune disorders. Despite recent scientific advances, patient access to these agents can be limited. Biosimilars are designed to be highly similar to the originator biologic, targeting the same biological pathways, with comparable efficacy and safety. Biosimilars have the advantage of lower treatment costs, offering the potential for increased clinical use and patient access. Several biosimilars are approved for clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Yet, an open and positive attitude should be adopted by all healthcare providers (i.e., physicians, nurses, and pharmacists) who communicate with patients. This involves empathy, reassurance, and nonverbal elements in their communication towards patients when discussing medicines in general [51,62]. It will be essential to educate HCPs using these communication techniques or 'soft skills' in the future.…”
Section: Communicate Positivelymentioning
confidence: 99%
“…Yet, an open and positive attitude should be adopted by all healthcare providers (i.e., physicians, nurses, and pharmacists) who communicate with patients. This involves empathy, reassurance, and nonverbal elements in their communication towards patients when discussing medicines in general [51,62]. It will be essential to educate HCPs using these communication techniques or 'soft skills' in the future.…”
Section: Communicate Positivelymentioning
confidence: 99%
“…Biosimilars must have the same therapeutic indications, mechanism of action, route of administration, dosage form and strength as the reference product. Some minor differences in clinically inactive components may be allowed, as long as they do not affect the drug safety (10).…”
Section: Biologics and Biosimilarsmentioning
confidence: 99%
“…Furthermore, various studies have identified significant gaps in the knowledge of healthcare professionals concerning biosimilars; therefore, it is important to increase awareness and inform professionals that the approval of biosimilars is based on reliable scientific data and clinical trials (14). Both the European Society for Medical Oncology and the American Society of Oncology have developed guidelines to assist healthcare professionals and enhance their confidence in prescribing biosimilars (10). Furthermore, in Australia, a significant effort has been made to alleviate misconceptions regarding biosimilars, with the government spending AU$20 million on this issue (13).…”
Section: Biologics and Biosimilarsmentioning
confidence: 99%
See 2 more Smart Citations